Implementasi Strategi Brain Break dan Ice Breaking dalam Meningkatkan Motivasi dan Keterlibatan Belajar Siswa Kelas I Madrasah Ibtidaiyah - Alfani, Moch. Farich; Hidayati, Lili (Ibtida'iy : Jurnal Prodi PGMI, 2026)
Learning in lower grades, especially grade I of Madrasah Ibtidaiyah, requires strategies that can maintain students' concentration and enthusiasm for learning. Early childhood tends to get bored easily, so a fun and varied learning approach is needed. Indicators of enthusiasm for learning can be seen from various aspects such as paying attention to learning with focus, asking questions when not understanding the material, and submitting assignments on time. This study aims to describe the application of brain break and ice breaking strategies in maintaining enthusiasm for teaching and learning in grade I MI Tamrinussibyan 1 Al-Hikmah. The research method used is a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the application of brain break and ice breaking strategies can create a more enjoyable learning atmosphere, increase focus, and foster student enthusiasm in participating in teaching and learning activities. In addition, this strategy helps teachers in managing the class and reduces student boredom during the learning process. Thus, the application of brain break and ice breaking strategies has proven effective in maintaining enthusiasm for teaching and learning in grade I MI Tamrinussibyan 1 Al-Hikmah.